Picking Optimization in a Peruvian SMEs Based on Lean Warehousing Techniques - Barrantes Rosas, Daniela (2023)
Picking is a basic process within warehouse management, comprising the activities carried out since the order is received until the products are located in the warehouse and are ready for dispatch. The objective of this study was to optimize the productivity of the picking process in a Peruvian food company. For this purpose, a pre-test and post-test methodology was designed with a qualitative and descriptive approach in order to suggest an innovative proposal. Lean Warehousing techniques, such as 5s and Systematic Layout Planning (SLP) were utilized, as well as an inventory record automation model and ADKAR, a change management model. The proposal was validated through pilot tests and a simulation in the Arena software (16.1 version), proving its effectiveness in increasing productivity by more than 36%. The value of this study lies in that it can be applied both in companies in the same sector or other areas that have their own warehouse and want to increase its productivity.